Christianiser la Révolution mexicaine : l’idéologie de l’Union Nationale des Étudiants Catholiques (années 1930) - Romain Robinet (Nuevo mundo - Mundos Nuevos, 2016)
This contribution analyses the ideology of the National Catholic Student Union (UNEC), a Mexican organization created in 1931 and which lasted until the beginning of the 1940s. This confessional association was supervised by the Company of Jesus and served the interests of the Mexican church, which was deeply weakened at that time. Well-known for having been one of the antechambers of the National Action Party in 1939, the UNEC quickly developed a coherent and genuine ideological system to cope with the Mexican Revolution. Defining itself as catholic and revolutionary, the student organization succeeded in reconciling the Catholic Social Doctrine and the reformist proposals of the Mexican Revolution (in terms of agrarian reform and labor legislation). At the same time, the UNEC developed a selective reading of the Revolution which clearly rejected every laic or anticlerical aspects included in this process.